DINAS KEBUDAYAAN DAN PARIWISATA DALAM PENGEMBANGAN KAWASAN TEPIAN SUNGAI SIAK - Alan Budianto; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Siak River is a historical site in Pekanbaru and the Kingdom of Siak Indrapura, and the deepest in Indonesia. While on the banks of the Siak River, there are still a lot of heritage in the form of houses on stilts, historical homestay, pasar bawah market, rubber factory, old terminal, historical grave, mosque and many more. But unfortunately, the lack of utilization of the potential of Siak River banks by the Department of Culture and Tourism Pekanbaru City made it not optimally utilized. Can be seen from inadequate supporting facilities, lack of role and public awareness, lack of promotion, limited human resources, constrained land acquisition and lack of budget. Department of Culture and Tourism Pekanbaru City seeks to develop the Siak River banks into a tourist destination object. This study aims to determine the efforts of the Department of Culture and Tourism in developing the Siak River banks and the factors inhibiting the development of the siak river banks.The theory used is the theory by Suwantoro which are tourism object and attraction, tourist infrastructure, tourism facilities, management or infrastructure, and society or the environment. In this study the authors used descriptive qualitative research methods with the location of research at the Department of Culture and Tourism Pekanbaru City and the key informant is the head section of facilities and infrastructure Department of Culture and Tourism. The Data collection techniques were interviews, observation and documentation.From the results of this study it can be known that the development of Siak River banks has not been maximized. It can be seen from the lack of facilities and infrastructure, limited supporting facilities such as entertainment facilities and tourist attractions. The factors that hamper the efforts of the Department of Culture and Tourism in the Development of Siak River banks is the lack of funds from the City Government, especially for tourism development, constrained land acquisition, most of the land ownership status owned by residents around the edge has not reached the certification stage Recorded at City BPN (HM, HGB, HGL, etc).Keywords: Regional development, Tourism development, Inhibiting factors